2007
DOI: 10.1108/14626000710727917
|View full text |Cite
|
Sign up to set email alerts
|

A supplier development programme: the SME experience

Abstract: Purpose -The purpose of this paper is to identify and understand the learning opportunities that exist for smaller organisations within the context of a supplier development and business improvement environment. Design/methodology/approach -Through case study research two pilot activities are presented. These are co-ordinated by a lead organisation (customer) and involve two micro firm suppliers. Findings -The research discusses the types of learning identified within two pilot activities and the benefits and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…In turn, the buyers would work with a smaller number of suppliers. Supplier integration makes it possible to source more efficiently and is often described as a buyer's competitive edge (Kannan and Tan, 2004;Lee-Mortimer, 1994;Theodorakioglou et al, 2006;Wagner, 2006;Williams, 2007). This approach results not only in closer-knit buyersupplier relationships, but also in a greater interdependence of both corporations.…”
Section: Corporate Partnerships and Supplier Developmentmentioning
confidence: 97%
“…In turn, the buyers would work with a smaller number of suppliers. Supplier integration makes it possible to source more efficiently and is often described as a buyer's competitive edge (Kannan and Tan, 2004;Lee-Mortimer, 1994;Theodorakioglou et al, 2006;Wagner, 2006;Williams, 2007). This approach results not only in closer-knit buyersupplier relationships, but also in a greater interdependence of both corporations.…”
Section: Corporate Partnerships and Supplier Developmentmentioning
confidence: 97%
“…In particularly, they ascertained that joint action and trust emerged as important factors for increasing the operational performance of buying firms. Williams (2007) investigated supplier development programs in SMEs. He found that suppliers and buyers are able to share knowledge and this can be advantageous to the community of SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different learning activities through mutual information exchange have radical impacts on supplier development efficiency [5]. The learning activities are either single or double loop in which the former is achieved by training methods but the latter is more elusive as it is more challenging to the existing process.…”
Section: Elements and Practices Of Supplier Developmentmentioning
confidence: 99%
“…There have been different studies which indicate the proper management of supplier relationships constitutes one essential element on supply chain success [1][2][3][4]. The literature has emphasized greater collaboration between the firms and their suppliers to assure an efficient and successful supply chain [5].…”
Section: Introductionmentioning
confidence: 99%